Cardpe: Assessing the market potential in a dynamic payments ecosystem in India - SINDHWANI, Saumya (Institutional Knowledge at Singapore Management University, 2017)
Set in December 2016, the case follows Sumeet Mehta, CEO of Cardpe Services Private Ltd, a fintech startup established to tap into the gap that existed in the payments acceptance infrastructure in India. Cardpe was all set to launch a mobile Point-of-Sale (mPOS) device – a wireless handheld integrated unit - that processed credit/debit card payments. Cash was a predominant medium of transaction in the country but the government was accelerating digitalisation and promoting measures to move towards a less-cash economy. Measures were underway to bring the largely unbanked public into banking network. Correspondingly, debit and credit card issuance was also growing. However, the availability of point-of-sale (POS) devices that could process credit/debit card payments was inadequate and remained concentrated among large merchants in cities. Due to this shortfall, the use of cards for payments remained low. Cardpe intended to target the merchants in the Tier II and Tier III cities, which were largely ignored by the acquiring banks, aggregators and the electronic wallet companies. Mehta had to assess the market potential for mPOS in the increasingly crowded market and to evaluate the odds stacked against Cardpe in the target market and as he re-examines Carpe’s go-to-market strategy. This case offers an opportunity to learn about the innovation adoption model and the challenges involved in altering market behaviour; and devising marketing strategy to overcome barriers involved in product adoption. The case would also help students to understand how to apply and integrate market data and information on evolving scenarios to estimate the market size for a product/service.